Phylogenetic evidence for an expanded circumscription of Gabura (Arctomiaceae). (January 2020) - Magain, Nicolas; Spribille, Toby; DiMeglio, Joseph; Nelson, Peter R.; Miadlikowska, Jolanta; Sérusiaux, Emmanuël
Abstract: Since the advent of molecular taxonomy, numerous lichen-forming fungi with homoiomerous thalli initially classified in the family Collemataceae Zenker have been transferred to other families, highlighting the extent of morphological convergence within Lecanoromycetes O. E. Erikss. & Winka. While the higher level classification of these fungi might be clarified by such transfers, numerous specific and generic classifications remain to be addressed. We examined the relationships within the broadly circumscribed genus Arctomia Th. Fr., which has been the recipient of several transfers from Collemataceae . We demonstrated that Arctomia insignis (P. M. Jørg. & Tønsberg) Ertz does not belong to Arctomia s. str. but forms a strong monophyletic group with Gabura fascicularis (L.) P. M. Jørg. We also confirmed that Arctomia borbonica Magain & Sérus. and the closely related Arctomia insignis represent two species. We formally transferred A. insignis and A. borbonica to the genus Gabura Adans. and introduced two new combinations: Gabura insignis and Gabura borbonica . We reported Gabura insignis from Europe (Scotland and Ireland) for the first time. While material from Europe and North America is genetically almost identical, specimens from Madagascar, South Africa and Reunion Island belong to three distinct phylogenetic lineages, all of which are present in the latter area and may represent distinct species. In its current circumscription, the genus Gabura may contain up to six species, whereas Arctomia s. str. includes only two species ( A. delicatula Th. Fr. and A. teretiuscula P. M. Jørg.). The Gabura insignis group is shown to have an unexpectedly large, subcosmopolitan distribution. With the extended sampling from Arctomiaceae Th. Fr., the placement of Steinera sorediata P. James & Henssen in the genus Steinera Zahlbr. is confirmed and the presence of a new Steinera species from Chile is highlighted.